Bad karma. (1st December 2013) - Senn, Stephen; Leventhal, Phillip
<x xml:space="preserve">Abstract</x> Bad Pharma provides a hyper-critical account of the pharmaceutical industry's approach to conducting, publishing and using clinical research and development. However, its attack on the drug regulators is unfair and its examination of the medical press uncritical. In consequence, it fails to provide the appropriate solution to making results of trials more widely available. This is to make the rigour of drug regulation available to all, rather than extending the use of that mediocre medium, the medical press.